Heat transfer and pressure drop characteristics of hybrid Al₂O₃-SiO₂ / Muyassarah Syahirah Mohd Yatim ...[et al.] - Mohd Yatim, Muyassarah Syahirah; Zakaria, Irnie Azlin; Roslan, Mohamad Fareez; Wan Mohamed, Wan Ahmad Najmi (Universiti Teknologi MARA, 2021)
The emergence of Proton Electrolyte Membrane Fuel Cell (PEMFC) is seen as one of the greener alternatives to internal combustion engine (ICE) in automotive industry nowadays. However, the sensitivity of a PEMFC membrane needs to be further improved for the optimum performance. In this study, single and hybrid nanofluids are used as an alternative coolant in a single channel of PEMFC. The study was conducted in a channel with the adoption of single and hybrid nanofluids to observe the effect of the heat transfer and pressure drop in the set up. A heater pad was kept at constant heat load of 100 W, reflecting the actual heat load of a single cell. The study focuses on 0.5% volume concentration for single and hybrid nanofluids of Al2O3 and SiO2 in water. The numerical study was conducted via ANSYS FLUENT 16.0. The 0.5% hybrid Al2O3:SiO2 nanofluids of 10:90 and 30:70 in Re range of 300 to 1000 were compared to the base fluid. The heat transfer increament of 9.1% and 9.85%. was observed. However, the pressure drop was also increased in the range of 22 Pa to 26 Pa for 0.5 % of Al2O3:SiO2 of 10:90 and 30:70 consecutively as compared to the base fluid. The advantage ratio was then analyzed to show the feasibility of both ratios of 0.5 % hybrid nanofluid of Al2O3:SiO2 at 10:90 and 30:70. It shows that both have advantage ratio higher than 1, thus feasible for the adoption in a PEMFC.